MANAJEMEN EMOSI GURU PAUD DALAM PENGELOLAAN SDM DI BIDANG PENDIDIKAN DAN PERSPEKTIF PSIKOLOGI - Lisdayanti Aulia Putri, Lisda Aulia; Syahrial Shaddiq, Syahrial Shaddiq (Integrative Perspectives of Social and Science Journal, 2025)
Early childhood has unique developmental characteristics and requires an emotionally sensitive approach. PAUD teachers are the main companions of children in their golden age. Facing various challenges in managing children's behavior and emotions, which also affect the teacher's own personal emotions. This journal discusses the importance of emotional management for early childhood education teachers in dealing with work pressure, class dynamics, and children's needs. This study refers to the theory of human resource management in the fields of education and psychology. The ability of teachers to recognize, manage and express emotions in a healthy manner is key to creating a harmonious learning environment and supporting the optimal development of children. This journal recommends the importance of training and psychological support for PAUD teachers in order to improve human resource management in PAUD institutions